Does Posterior Cervical Decompression Conducted by Junior Surgeons Affect Clinical Outcomes in the Treatment of Cervical Spondylotic Myelopathy? Results From a Multicenter Study. Issue 1 (February 2019) - Nagoshi, Narihito; Iwanami, Akio; Isogai, Norihiro; Ishikawa, Masayuki; Nojiri, Kenya; Tsuji, Takashi; Daimon, Kenshi; Takeuchi, Ayano; Tsuji, Osahiko; Okada, Eijiro; Fujita, Nobuyuki; Yagi, Mitsuru; et al.
Study Design: Retrospective multicenter study. Objectives: To evaluate the outcomes of posterior cervical decompression for cervical spondylotic myelopathy (CSM) when performed by board-certified spine (BCS) or non-BCS (NBCS) surgeons. Methods: We reviewed outcomes for 675 patients who underwent surgery for CSM, were followed at least 1 year after surgery, and were assessed preoperatively and at final follow-up by Japanese Orthopaedic Association (JOA) scores and by the visual analog scale (VAS) for the neck. Cervical alignment was assessed on radiographs by C2-C7 angles, and range of motion (ROM) by extension minus flexion C2-C7 angles. We compared outcomes for BCS surgeons, who must meet several requirements, including experience in more than 300 spinal surgeries, and for NBCS surgeons. Results: BCS surgeons performed 432 of 675 laminoplasties. NBCS surgeons were primary in 243 surgeries, of which 187 were directly supervised by a BCS surgeon. BCS surgeons required significantly less time in surgery (98.0 ± 39.5 vs 108.1 ± 49.7 min; P < .01). BCS and NBCS surgeons had comparable perioperative complications rates, and preoperative-to-postoperative changes in JOA scores (2.9 ± 2.1 vs 3.1 ± 2.3; P = .40) and VAS (−1.5 ± 2.9 vs −1.4 ± 2.5; P = .96). Lordotic cervical alignment and ROM were maintained after operations by both groups. Conclusions: Surgical outcomes such as functional recovery, complication rates, and cervical dynamics were comparable between the BCS and NBCS groups. Thus, posterior cervical decompression for CSM is safe and effective when performed by junior surgeons who have been trained and supervised by experienced spine surgeons.